2010
DOI: 10.1186/ar3056
|View full text |Cite
|
Sign up to set email alerts
|

Reduced trabecular bone mineral density and cortical thickness accompanied by increased outer bone circumference in metacarpal bone of rheumatoid arthritis patients: a cross-sectional study

Abstract: IntroductionThe objective of this study was to assess three-dimensional bone geometry and density at the epiphysis and shaft of the third meta-carpal bone of rheumatoid arthritis (RA) patients in comparison to healthy controls with the novel method of peripheral quantitative computed tomography (pQCT).MethodsPQCT scans were performed in 50 female RA patients and 100 healthy female controls at the distal epiphyses and shafts of the third metacarpal bone, the radius and the tibia. Reproducibility was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
3
30
0
2
Order By: Relevance
“…This protocol allows accurate measurements of volumetric BMD and cross-sectional geometry at the distal epiphysis and shaft of the third metacarpal bone. At the radius, the tibia, and the third metacarpal bone, we have found epiphyseal trabecular BMD and shaft cortical thickness to be reduced in female RA patients compared to healthy controls (13). While existing studies have shown that bone mass at the metacarpal bone shaft of RA patients is reduced (15), and its cross-sectional geometry different from healthy controls (13), it has not been assessed whether these differences may be due to the Metacarpal bone measurements.…”
Section: Introductionmentioning
confidence: 73%
“…This protocol allows accurate measurements of volumetric BMD and cross-sectional geometry at the distal epiphysis and shaft of the third metacarpal bone. At the radius, the tibia, and the third metacarpal bone, we have found epiphyseal trabecular BMD and shaft cortical thickness to be reduced in female RA patients compared to healthy controls (13). While existing studies have shown that bone mass at the metacarpal bone shaft of RA patients is reduced (15), and its cross-sectional geometry different from healthy controls (13), it has not been assessed whether these differences may be due to the Metacarpal bone measurements.…”
Section: Introductionmentioning
confidence: 73%
“…Studies of patients with other chronic inflammatory conditions, particularly inflammatory bowel disease [20,21] and rheumatoid arthritis [22], have demonstrated a similar pattern of trabecular bone loss and endocortical thinning. The higher levels of TNF-α among coinfected participants further suggests the contribution of chronic inflammation.…”
Section: Discussionmentioning
confidence: 91%
“…Our analyses focused on women because associations between HIV/HCV coinfection and low BMD have been stronger in women than in men [12,14]. We hypothesized that coinfected women would have lower trabecular volumetric BMD and cortical thinning due to endocortical bone loss, a pattern observed in other chronic inflammatory diseases [20][21][22], compared with HCV-or HIV-monoinfected women and those without a history of either infection.…”
mentioning
confidence: 99%
“…Their coefficient of variation (CV%) of about 0.4% (8,9) compares favorably with the approximately 0.9% of dual energy X-ray absorptiometry (DXA) of the hand (10), the 0.7% of computed tomography (CT) (11) and the 1-3% of DXA hip (12). The high reproducibility of DXR makes it suitable for evaluating treatment effect, because very small changes in BMD can be detected with a high statistical power.…”
Section: Introductionmentioning
confidence: 96%